Deuterium Metabolic Imaging Enables the Tracing of Substrate Fluxes Through the Tricarboxylic Acid Cycle in the Liver - Ehret, Viktoria; Dürr, Sabine C; Ustsinau, Usevalad; Friske, Joachim; Scherer, Thomas; Fürnsinn, Clemens; Starčuková, Jana; Helbich, Thomas H; Philippe, Cécile; Krššák, Martin (NMR in biomedicine, 2025)
Alterations in tricarboxylic acid (TCA) cycle metabolism are associated with hepatic metabolic disorders. Elevated hepatic acetate concentrations, often attributed to high caloric intake, are recognized as a pivotal factor in the etiology of obesity and metabolic syndrome. Therefore, the assessment of acetate breakdown and TCA cycle activity plays a central role in understanding the impact of diet-induced alterations on liver metabolism. Magnetic resonance-based deuterium metabolic imaging (DMI) could help to unravel the underlying mechanisms involved in disease development and progression, however, the application of conventional deuterated glucose does not lead to substantial enrichment in hepatic glutamine and glutamate. This study aimed to demonstrate the feasibility of DMI for tracking deuterated acetate breakdown via the TCA cycle in lean and diet-induced fatty liver (FL) rats using 3D DMI after an intraperitoneal infusion of sodium acetate-d3 at 9.4T. Localized and nonlocalized liver spectra acquired at 10 time points post-injection over a 130-min study revealed similar intrahepatic acetate uptake in both animal groups (AUCFL = 717.9 ± 131.1 mM▯min-1, AUClean = 605.1 ± 119.9 mM▯min-1, p = 0.62). Metabolic breakdown could be observed in both groups with an emerging glutamine/glutamate (Glx) peak as a downstream metabolic product (AUCFL = 113.6 ± 23.8 mM▯min-1, AUClean = 136.7 ± 41.7 mM▯min-1, p = 0.68). This study showed the viability of DMI for tracking substrate flux through the TCA cycle, underscoring its methodological potential for imaging metabolic processes in the body.
Keywords: Liver; Citric Acid Cycle; Rats; játra; Metabolic Flux Analysis; potkani Sprague-Dawley; deuterium; Rats, Wistar; mužské pohlaví; Acetates; krysa rodu Rattus; magnetická rezonanční tomografie; Magnetic Resonance Imaging; zvířata; acetáty; analýza metabolického toku; Rats, Sprague-Dawley; citrátový cyklus; potkani Wistar; Deuterium; Male; Animals